2014
DOI: 10.1093/pcp/pcu151
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Decapping Enzyme DCP2 Accumulates in DCP1 Foci Under Heat Stress in Arabidopsis thaliana

Abstract: The decapping enzymes DCP1 and DCP2 are components of a decapping complex that degrades mRNAs. DCP2 is the catalytic core and DCP1 is an auxiliary subunit. It has been assumed that DCP1 and DCP2 are consistently co-localized in cytoplasmic RNA granules called processing bodies (P-bodies). However, it has not been confirmed whether DCP1 and DCP2 co-localize in Arabidopsis thaliana. In this study, we generated DCP1-green fluorescent protein (GFP) and DCP2-GFP transgenic plants that complemented dcp1 and dcp2 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 59 publications
6
32
0
1
Order By: Relevance
“…After cycloheximide treatment, which causes loss of P-bodies (Sheth and Parker, 2003), no cytoplasmic foci were observed in any case, suggesting that the detected LSM1-GFP spots indeed corresponded to P-bodies (Figures 1C; Supplemental Figure 2B). The identity of these foci was confirmed by colocalization studies with DCP1, a protein that accumulates in P-bodies (Xu et al, 2006;Weber et al, 2008;Motomura et al, 2015). The examination of LSM1A PRO -LSM1A-GFP and LSM1B PRO -LSM1B-GFP plants cotransformed with a 35S-RFP-DCP1 fusion (Perea-Resa et al, 2012) demonstrated that, in fact, LSM1A-GFP and LSM1B-GFP colocalized with RFP-DCP1 in root cells exposed to 4°C ( Figure 1D).…”
Section: Arabidopsis Lsm1 Proteins Localize To P-bodies In Response Tmentioning
confidence: 68%
See 2 more Smart Citations
“…After cycloheximide treatment, which causes loss of P-bodies (Sheth and Parker, 2003), no cytoplasmic foci were observed in any case, suggesting that the detected LSM1-GFP spots indeed corresponded to P-bodies (Figures 1C; Supplemental Figure 2B). The identity of these foci was confirmed by colocalization studies with DCP1, a protein that accumulates in P-bodies (Xu et al, 2006;Weber et al, 2008;Motomura et al, 2015). The examination of LSM1A PRO -LSM1A-GFP and LSM1B PRO -LSM1B-GFP plants cotransformed with a 35S-RFP-DCP1 fusion (Perea-Resa et al, 2012) demonstrated that, in fact, LSM1A-GFP and LSM1B-GFP colocalized with RFP-DCP1 in root cells exposed to 4°C ( Figure 1D).…”
Section: Arabidopsis Lsm1 Proteins Localize To P-bodies In Response Tmentioning
confidence: 68%
“…Remarkably, however, Arabidopsis LSM1 proteins were found to localize to P-bodies in response to the different stresses assayed, indicating that the molecular mechanisms mediating LSM1 localization to these foci do not depend on protein levels. In this way, DCP1 has also been reported to localize to P-bodies under stress conditions even though its levels do not increase (Motomura et al, 2015). These findings suggest that the localization of LSM1 to P-bodies, like that of DCP1 and other Arabidopsis RNA decayrelated proteins (Merret et al, 2013;Motomura et al, 2015), is induced in plants exposed to abiotic stresses.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…All three proteins are considered core decapping complex factors, indispensable for mRNA decapping and essential for postembryonic development (Xu and Chua, 2011). Colocalization of AtDCP1 and AtDCP2 in macromolecular foci detectable by confocal microscopy is dynamically regulated by heat stress (Motomura et al, 2015). Based on mutant analyses, the factor VCS regulates seed dormancy and germination in Arabidopsis (Basbouss-Serhal et al, 2017) and functions in plant-fungal pathogen interactions in Nicotiana benthamiana (Petre et al, 2016).…”
Section: Decappingmentioning
confidence: 99%
“…11,12 Second, treatment with cycloheximide, which causes trapping of mRNA in polysomes by inhibiting the translocation step during the elongation phase in protein synthesis, abolished SG and PB assembly. 11,13 By performing a co-localization study using SG-and PB-associated proteins eIF4e and DCP1, respectively, we have revealed that these RNP complexes are situated in close proximity to each other in Arabidopsis root cells under heat stress (Fig. 1, arrowheads).…”
mentioning
confidence: 95%